2016
DOI: 10.1016/j.jecp.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Visual access trumps gender in 3- and 4-year-old children’s endorsement of testimony

Abstract: Several studies have investigated how preschoolers weigh social cues against epistemic cues when taking testimony into account. For instance, one study showed that 4- and 5-year-olds preferred to endorse the testimony of an informant who had the same gender as the children; by contrast, when the gender cue conflicted with an epistemic cue--past reliability--the latter trumped the former. None of the previous studies, however, has shown that 3-year-olds can prioritize an epistemic cue over a social cue. In Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
5
26
0
3
Order By: Relevance
“…To our knowledge and following a review of the literature, this is the first time that such a sex bias has been observed (see electronic supplementary material, table S1). Previous studies have reported that children prefer to endorse information coming from informants of their own sex [ 49 ], which may eventually result in sex differences when it comes to overimitation in adults: women have indeed been observed to copy more precisely and more rapidly irrelevant tool actions performed by male models than female models [ 50 ]. However, in our study the Serbian children were all tested by female experimenters and showed the same sex bias as the French children (tested by one male experimenter), thus the sex of the model is unlikely to have played a role in our results.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge and following a review of the literature, this is the first time that such a sex bias has been observed (see electronic supplementary material, table S1). Previous studies have reported that children prefer to endorse information coming from informants of their own sex [ 49 ], which may eventually result in sex differences when it comes to overimitation in adults: women have indeed been observed to copy more precisely and more rapidly irrelevant tool actions performed by male models than female models [ 50 ]. However, in our study the Serbian children were all tested by female experimenters and showed the same sex bias as the French children (tested by one male experimenter), thus the sex of the model is unlikely to have played a role in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Epistemic and social characteristics are both important to children’s strategies for selecting and trusting informants. Moreover, these two types of characteristics also interact with each other (e.g., Terrier, Bernard, Mercier, & Clément, ). For instance, Corriveau and Harris () found that seeing a familiar teacher inaccurately label familiar objects undermined 4‐ to 5‐year‐old preschoolers’ trust in her labels for unfamiliar objects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we know that dominance plays a crucial role in young children's social lives, that they can infer dominance from various cues, and make various inferences from dominance. Moreover, young children have been shown to take other social cues into account when evaluating testimony, even when those cues do not have obvious epistemic value like gender (Terrier, Bernard, Mercier, & Clément, 2016) or minimal group membership (MacDonald, Schug, Chase, & Barth, 2013).…”
mentioning
confidence: 99%